PHYSIOLOGICAL VOCAL WARMING UP PROGRAM IN RELIGIOUS SINGERS - Cristina da Costa Santana Nicoletti, Daniella; Cristina Munzlinger Dos Santos, Andréia; Biaggi Alves de Alencar, Priscila (Health and Society, 2021)
Purpose: To analyze the effectiveness of a physiological vocal warm-up program focused on religious singers. Method: longitudinal study involving 39 subjects male and female, aged at least 18 and at most 50, the participants underwent an evaluation vocal pre-warm-up and vocal post-warm-up, results being compared to both evaluations. The evaluation was applied questionnaire vocal habits and symptoms, acoustic analysis and auditory perceptual analysis. The study was conducted in Catholic Churches of Várzea Grande City in the state Mato Grosso. Results: They said participants to use the corner of a median of 87.3 months with weekly frequency of 2.4 times per week. However, 89.7% of the singers reported not warm up the voice before the corner and not desaquecerem 94.9% after the corner. In inadequate vocal habits most said talking aplenty. Already in vocal symptoms the three most prevalent were: voice worse in the morning (59.0%), loss of treble (54.4%) and hoarseness constant (51.3%). After application of vocal warm-up program improvement was observed in vocal self assessment and auditory perceptual analysis. There was also a significant increase in the fundamental frequency of the sustained vowel, but for the singing voice there was no change in acoustic parameters analyzed. Conclusion: The vocal heating program was effective with positive changes in voice adjustments, providing a more comfortable voice output this being noticed by singers themselves.